Knowledge-based power system protection design courseware - Othman, Mohammad Lutfi; Aris, Ishak; Mariun, Norman; Sahbudin, Ratna Kalos Zakiah (Asian Network for Scientific Information, 2006)
This research discusses the development of a knowledge-based expert system, using an interactive multimedia approach and its usage to serve as a multimedia courseware in power system protection design. The system is characterized by its three prong capabilities: multimedia interactive, knowledge based and numerical analysis ready. It integrates technical theories, industrial application recommendations and some specific simulations by which the user has a wide range of choices for obtaining technical information on power system protection. Being an interactive computer-assisted learning tool, the system blends power system protection knowledge domain and interactivity knowledge. Survey results concerning the acceptability of this courseware prove that it is very useful to the users in so far as its performance and effectiveness as a teaching and training tool in the power system protection knowledge is concerned. © 2006 Asian Network for Scientific Information